2016
DOI: 10.1186/s11658-016-0004-2
|View full text |Cite
|
Sign up to set email alerts
|

The crucial role of miR-126 on suppressing progression of esophageal cancer by targeting VEGF-A

Abstract: BackgroundmiR-126 is a key regulator of oncogenic processes. It is functionally linked to cellular proliferation, survival and migration. Vascular endothelial growth factor A (VEGF-A), which is regarded as a tumorgenesis activator, could directly target miR-126 in several tumors. However, the mechanism in esophageal cancer remains unclear.Methods and resultsIn this study, the expression of miR-126 and VEGF-A were assessed in esophageal cancer tissues and esophageal cancer cell lines. We found that miR-126 has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…HOTAIR is a 2148‐nucleotide‐long lncRNA that has been shown to participate in the development of the physiological epidermis as well as the progression of cancer, and potentially as a regulator of tumour suppressor genes . Apart from lncRNA, accumulating evidence has highlighted the crucial inhibitory role of miRs in blocking the development of oesophageal cancer, such as microRNA‐204 (miR‐204), which performs as a tumour suppressor . HOTAIR has been reported to influence the progression of oesophageal squamous cell carcinoma by binding to endogenous miR‐125 and miR‐143 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HOTAIR is a 2148‐nucleotide‐long lncRNA that has been shown to participate in the development of the physiological epidermis as well as the progression of cancer, and potentially as a regulator of tumour suppressor genes . Apart from lncRNA, accumulating evidence has highlighted the crucial inhibitory role of miRs in blocking the development of oesophageal cancer, such as microRNA‐204 (miR‐204), which performs as a tumour suppressor . HOTAIR has been reported to influence the progression of oesophageal squamous cell carcinoma by binding to endogenous miR‐125 and miR‐143 .…”
Section: Introductionmentioning
confidence: 99%
“…12 Apart from lncRNA, accumulating evidence has highlighted the crucial inhibitory role of miRs in blocking the development of oesophageal cancer, such as microRNA-204 (miR-204), which performs as a tumour suppressor. [13][14][15][16] HOTAIR has been reported to influence the progression of oesophageal squamous cell carcinoma by binding to endogenous miR-125 and miR-143. 17 Besides, studies have also suggested that HOTAIR regulates HOX genes, 18,19 whose expression has been detected in oesophageal cancer cell lines, including HOXC8.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing VEGF expression is directly proportional to increasing tumor growth and metastasis by promoting angiogenesis and increasing vascular permeability . The role of VEGF in angiogenesis was further confirmed by the effects of hypoxia and several indirect effects of pro‐angiogenic factors, which were able to further increase the synthesis of VEGF . It is important that VEGF has also been associated with tumor progression by stimulating angiogenesis in human esophageal carcinoma …”
Section: Discussionmentioning
confidence: 90%
“…16 The role of VEGF in angiogenesis was further confirmed by the effects of hypoxia and several indirect effects of proangiogenic factors, which were able to further increase the synthesis of VEGF. 17,18 It is important that VEGF has also been associated with tumor progression by stimulating angiogenesis in human esophageal carcinoma. 19,20 IL-1RA is a member of the interleukin-1 family.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR‐126 has a crucial function as a cancer‐suppressive miRNA in different kinds of tissues, including the pancreas, liver, and lung . In lung carcinoma cells, miR‐126 expression is inhibited, leading to the upregulation of target genes encoding VEGF . Smoking has a significant effect on the expression of 133 miRNAs in the lung tissue of rats, and some of these miRNAs may be involved in carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%